Intensity of a training session during Ramadan in fasting and non-fasting Tunisian youth football players - Leiper, J. B.; Watson, P.; Evans, G.; Dvorak, J. (Journal of Sports Sciences, 2008)
Heart rate was measured in 79 young male soccer players during training in the third week of Ramadan. Forty-eight players were practising Ramadan fasting, while the other 31 players were eating normally. All participants trained for 60-80 min at an ambient temperature of 25-28°C and relative humidity of 50-53%. Heart rate, which was measured throughout the training session, was marginally higher in the fasting (mean 144 beats/min, s = 25) than in the non-fasting (139 beats/min, s = 23) group (P < 0.001). When assessed as the percentage of heart rate reserve utilized, however, the training load was similar for both groups (62%, s = 8). No difference was detected in training intensity for the fasting and non-fasting groups when quantified by either training impulse (253, s = 139 and 253, s = 108, respectively) or training load indicator (222, s = 123 and 179, s = 49, respectively). The overall subjective rating of perceived exertion of the training session reported 20 min after finishing training was similar for the fasting (12, range 6-17) and non-fasting (12, range 7-17) groups, which was comparable (P = 0.16) to the mean value for the entire week (13, range 8-16). A similar finding was observed in the players' subjective appraisal of the difficulty of training of the individual session and for the whole week's training. Overall exercise load measures indicated that there was no biologically significant difference between the fasting and non-fasting groups during training in the third week of Ramadan.